Cooking Banana consumption patterns in the Plantaingrowing area of Southeastern Nigeria - Tshiunza, M.; Lemchi, J.; Onyeka, U.; Tenkouano, A. (2001)
Cooking bananas (Musa spp., ABB genome) were intro-duced into Southeastern Nigeria by the International Institute of Tropical Agriculture (IITA) in the mid-1980s as an interim measure to reduce the incidence of black sigatoka disease (caused by the fungus Mycosphaerel-la fijiensis Morelet) on plantain. However, the people of this region were not familiar with their utilisation methods. To address this lack of the knowledge and thereby sustain cooking banana cultivation, IITA, in collaboration with the Shell Petroleum Development Company (SPDC) and the Nigeria Agip OU Company (NAOC) commenced a training campaign on cooking banana processing methods. This study examined the patterns of utilisation of cooking bananas ten years after the training took place and compared them with plantain. About 95 % of the households interviewed are consuming cooking banana, indicating a broad acceptance of the crop in the region. Overall, two ripening stages termed green and ripe are the most popular ripening stages for the consumption of both plantain and cooking banana, followed by partially ripe maturity stage. The most common forms of consumption for green plantain are, in decreasing order of importance, pottage, boiled, roasted, and fried. Green cooking banana is also mostly eaten in pottage and boiled forms, and less frequently in fried and pounded forms. Ripe plantain is mostly eaten in fried and pottage forms, while ripe cooking banana is mostly eaten in fried and raw forms. Partially ripe plantain is mostly eaten in pottage, fried, boiled, and roasted forms, while partially ripe cooking banana is eaten in fried, pottage and boiled forms. These results indicate that the consumption patterns of plantain and cooking banana are very similar. This similarity has greatly contributed to the rapid integration of cooking banana within the existing plantain consumption and cropping systems.